2002
DOI: 10.1111/j.1365-2621.2002.tb10307.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Peach Polyphenoloxidase by Exposure to Pulsed Electric Fields

Abstract: The effect of exponential decay pulsed electric fields on peach (var. Miraflores) polyphenoloxidase (PPO) was evaluated. Electric field intensities ranged from 2.18 to 24.30 kV/cm. Pulses of 0.02 and 0.08 ms width were applied in mono-and bipolar mode. A 70% maximum reduction in enzymatic activity was achieved after 5 ms using 0.02 ms width pulses in bipolar mode at 24.30 kV/cm. Peach PPO activity decreased following an exponential decay kinetic model. Rate constants ranged from 9.0 to 138 ms -1 in monopolar m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
51
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 17 publications
(4 reference statements)
10
51
0
3
Order By: Relevance
“…While some researchers found a high level of inactivation (88%) on orange juice with E = 35 kV cm -1 for 5 µs (Yeom, Streaker, Zhang, & Min, 2000) and 93.8% on tomato at 24 kV cm -1 (Giner et al, 2002), others found very low levels of inactivation of 10% (1000 pulses of 1 µs at 1 or 2 Hz and field strength up to 35 kV cm -1 ) on PME extracted from fresh juice and dissolved in buffer solution; even an increase level of PME was found in the freshly squeezed juice (Van Loey, Verachtert, & Hendrickx, 2001). …”
Section: Enzyme Activitymentioning
confidence: 99%
“…While some researchers found a high level of inactivation (88%) on orange juice with E = 35 kV cm -1 for 5 µs (Yeom, Streaker, Zhang, & Min, 2000) and 93.8% on tomato at 24 kV cm -1 (Giner et al, 2002), others found very low levels of inactivation of 10% (1000 pulses of 1 µs at 1 or 2 Hz and field strength up to 35 kV cm -1 ) on PME extracted from fresh juice and dissolved in buffer solution; even an increase level of PME was found in the freshly squeezed juice (Van Loey, Verachtert, & Hendrickx, 2001). …”
Section: Enzyme Activitymentioning
confidence: 99%
“…In peaches, the activity of PPO and POD has long been known and has still been widely studied (Reyes & Luh, 1960;Flurkey & Jen, 1978;Alba et al, 1996;Girner et al, 2002). For Brazilian cultivars, although thermal inactivation of PPO and POD in Granada clingstone peaches (Toralles et al, 2005) and even the potential for enzymatic browning of some Brazilian peach cultivars (Toralles et al, 2004) are known, there is very little literature pertaining to the thermal inactivation of other peach cultivars.…”
mentioning
confidence: 99%
“…Ciência Rural, v.41, n.6, jun, 2011. ao escurecimento enzimático, seja pela elevada concentração de compostos fenólicos e/ou atividade de enzimas oxidativas, com destaque para polifenoloxidases (PPO) e peroxidases (POD) (GIRNER et al, 2002).…”
Section: O Escurecimento Enzimático E O Amolecimento São As Principaiunclassified